Crowdsourcing and Digital Information: Looking for a Future Research Agenda - Fernando J. Garrigos-Simon; Yeamduan Narangajavana-Kaosiri (Information)
Crowdsourcing has become increasingly relevant in academic research due to its role in the evolving digital landscape, where information is a key driver of organizational performance. In a context dominated by emerging technologies and digital platforms, organizations are turning to external sources for data and idea generation. This paper offers a comprehensive review of the literature on crowdsourcing and digital information, using bibliometric techniques and qualitative analysis to identify major trends. The findings reveal several shifts in focus: from conceptual frameworks to practical applications; from customer participation to broader stakeholder involvement; and from general technological and managerial approaches to specific technologies and emerging perspectives in entrepreneurship and finance. The primary contributing disciplines are Computer Science, Engineering, and Information Science. Recent research (post 2023) emphasizes constructs such as “crowdfunding”, “digital platforms”, and “machine learning”, moving beyond earlier focuses like “citizen science” and “social media.” This review also reveals growing interest in managerial, medical, and cultural heritage applications, alongside a decline in research related to geography and crisis management over the past two years. This study enhances our understanding of current research directions and practical implications in crowdsourcing and digital information, offering valuable insights for both academics and practitioners.